Sharia Property Business Development Strategy (Case Study: Tasnim Property) - Tambunan, Sofyan Ahmadi; Fahmi, Idqan; Hartono, Sri (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. The Sharia property industry in Indonesia has increased exponentially in recent years. Many Association of Sharia Property Developers (ADPS) members have recorded significant home sales. However, it is different with Tasnim Property, which has experienced a decline in home sales. This research aims to analyze consumer behaviour in making home purchase decisions, analyze internal factors, analyze micro and macro external factors, formulate alternative strategies and formulate strategic priorities that can be applied to Tasnim Property's business development strategy. This research was conducted from November 2022 to September 2023 with quantitative and qualitative approaches. In consumer behaviour analysis, the sampling technique used voluntary sampling through an online survey involving 75 respondents, and data analysis used SEM-PLS to determine the direct effect of product, price, place and promotion variables on home purchase decisions. In the strategic management analysis, the sampling technique used purposive sampling involving 6 respondents. Data analysis used the IFE matrix, Porter's Five Forces, PESTLE, EFE matrix, IE matrix, SWOT and QSPM matrix. The results showed that the product and promotion variables significantly affected home purchasing decisions. In contrast, the price and place variables did not significantly affect home purchasing decisions. There are 8 alternative strategies that have been formulated, namely: (1) increasing cooperation with a large number of Sharia Property Agency partners, (2) a home sales strategy with a unit booking system through Virtual Reality technology, (3) increasing marketing activities through B2G, B2B and B2C cooperation offers, (4) recruiting professional and experienced CEOs in the property sector, (5) introducing Tasnim products by enlarging marketing areas, (6) implementing simplified licensing procedures through the OSS (Online Single Submission) application, related agencies in local governments and online PBG, (7) a strategy to buy materials directly from factories/distributors, and (8) establishing a research & development division. The priority strategy that can be recommended for Tasnim Property is to increase cooperation with many Sharia Property Agency partners. This strategy is essential for the company to increase the market share of Sharia property with more massive and vigorous marketing efforts. Keywords: Business development strategy, sharia property, strategy formulation, consumer behaviour, purchase decision Abstrak. Industri properti syariah di Indonesia mengalami peningkatan secara eksponensial dalam beberapa tahun terakhir. Banyak member Asosiasi Developer Properti Syariah (ADPS) berhasil membukukan rekor penjualan rumah dengan signifikan. Akan tetapi, berbeda dengan Tasnim Property yang mengalami penurunan penjualan rumah. Penelitian ini bertujuan untuk menganalisis perilaku konsumen dalam melakukan keputusan pembelian rumah, menganalisis faktor internal, menganalisis faktor eksternal mikro dan makro, merumuskan alternatif strategi dan merumuskan prioritas strategi yang dapat diterapkan dalam strategi pengembangan bisnis Tasnim Property. Penelitian ini dilakukan pada bulan November 2022 hingga September 2023 dengan pendekatan kuantitatif dan kualitatif. Pada analisis perilaku konsumen, teknik pengambilan sampel menggunakan voluntary sampling melalui survei online yang melibatkan 75 responden, dan analisis data menggunakan SEM-PLS untuk menguji pengaruh langsung variabel product, price, place dan promotion terhadap keputusan pembelian rumah. Pada analisis manajemen strategik, teknik pengambilan sampel menggunakan purposive sampling yang melibatkan 6 responden, dan analisis data menggunakan matriks IFE, Porter’s Five Forces, PESTLE, matriks EFE, matriks IE, SWOT dan matriks QSPM. Hasil penelitian menunjukkan bahwa variabel product dan promotion memiliki pengaruh yang signifikan terhadap keputusan pembelian rumah, sementara variabel price dan place tidak berpengaruh signifikan terhadap keputusan pembelian rumah. Terdapat 8 alternatif strategi yang telah dirumuskan yaitu (1) meningkatkan kerjasama dengan mitra Agency Property Syariah dalam jumlah yang banyak, (2) strategi penjualan rumah dengan sistem booking unit melalui teknologi Virtual Reality, (3) meningkatkan aktivitas pemasaran melalui penawaran kerjasama B2G, B2B dan B2C, (4) merekrut CEO profesional dan berpengalaman di bidang properti, (5) memperkenalkan produk Tasnim dengan memperbesar wilayah pemasaran, (6) penerapan penyederhanaan prosedur perizinan melalui aplikasi OSS (Online Single Submission), dinas terkait di pemerintah daerah dan PBG online, (7) strategi membeli bahan material langsung ke pabrik/distributor, dan (8) membentuk divisi research & development. Strategi prioritas yang direkomendasikan bagi Tasnim Property adalah meningkatkan kerjasama dengan mitra Agency Properti Syariah dalam jumlah banyak. Strategi ini sangat diperlukan perusahaan dengan tujuan untuk meningkatkan market share properti syariah dengan usaha pemasaran yang lebih masif dan gencar. Kata kunci: Strategi pengembangan bisnis, properti syariah, formulasi strategi, perilaku konsumen, keputusan pembelian